Does academic stress predict nursing students' healthy and unhealthy behaviour? - Quinto, Egdonna (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2024)
The study aimed to examine the effect of academic stress on the healthy and unhealthy behaviour of nursing students. To gain more understanding of the concepts, literatures were reviewed. The study used descriptive assessment and correlational research design. The population of the study was 228 nursing students of the Divine Word College of Laoag. The questionnaires were used to gather the data and weighted mean and analysis of variance (ANOVA) were utilized to analyze the data. The study found that the academic stress of students was high and healthy behavior was also high. While unhealthy behaviour was low. In terms of the correlation between academic stress and healthy behaviour, the results signify that taken together the three dimensions (external pressure and expectations, course requirement overload and examination, and self-efficacy) are not associated with healthy behaviour. However, taken separately, academic stress related to self-efficacy significantly influenced healthy behaviour. Higher self-efficacy predicts higher healthy behaviour. Further, concerning the correlation between academic stress and unhealthy behaviour, the finding reveals that both are significantly correlated. It means higher academic stress leads to unhealthy behaviour.